A Statistical Assessment of the Performance of FSV - Zhang, G.; Sasse, H.; Wang, L.; Duffy, A. (Applied Computational Electromagnetics Society Journal (ACES), 2021)
This paper assesses the performance of the feature selective validation (FSV) method by applying probability density functions to the FSV point-by-point analysis. As an augmentation to confidence histograms, probability density functions offer two advantages: they (1) provide the users of FSV with more subtle information about the quality of the data comparison and (2) make a statistical analysis of the FSV results available. The application of probability density functions in the verification of FSV is presented in this paper, which provides a quantitative measure to support the qualitative conclusions drawn in early publications on the FSV method used as a foundation for IEEE Std. 1597.1.